Effect of thermal radiation on natural convection of a nanofluid in a square cavity with a solid body - Qasem, Sayyedah A. (Thermal Science, 2021)
This investigation is to concentrate on the effect of thermal radiation on free convection of a Cu-water nanofluid in a differentially heated cavity containing a solid square block placed in the middle. The upper and lower dividers of the cavity are kept as thermally protected; The coupled equations of mass, momentum, and energy are governed the mathematical model. Finite difference method is used to solve the governing equations. All internal surfaces of the cavity are deemed as a diffused emitters and reflectors for radiation. The impacts of relevant parameters, the Rayleigh number (10(3) <= Ra <= 10(6)), volume fraction of nanoparticles (0.0 <= phi <= 0.04) and thermal radiation (Rd = 0, 1, 5, and 10), are explored. For various values of the flow parameters, the values for local and average Nusselt number are calculated. It is observed that the local and averaged Nusselt numbers are increased with an increase in the Rayleigh number and volume fraction of nanoparticles. Also, the temperature distribution of the fluid increases with an increase in the radiation parameter.